Comparing Efficacy of Online and In-Person Versions of a Training on U.S. Federal Wage and Hour, Child Labor Laws, and Hazardous Occupations Orders for Secondary School Professionals - Shendell, Derek G.; Apostolico, Alexsandra A.; Milich, Lindsey J.; Patti, Alexa A.; Kelly, Sarah W. (Frontiers in Public Health, 2016)
Background The New Jersey Safe Schools Program (NJSS) offers courses required for secondary school vocational–career–technical education teachers to become school-sponsored structured learning experience supervisors. The “Federal Wage and Hour and Child Labor Laws, Regulations and Hazardous Order Course” (FWH) was originally conducted in-person by U.S. Department of Labor-Wage and Hour Division from 2005 to Summer 2013, and then NJSS began conducting this course in-person (October 2013–April 2015). Staring in March 2015, this course was conducted online; beta-/pilot tests were conducted in Winter 2014–2015. Starting in May 2015, this course was offered exclusively online. This paper analyzes data from the in-person and online versions of the FWH, including overall course evaluation data comparing two versions with similar questions/constructs. Methods The New Jersey Safe Schools Program modifications to FWH included adding information regarding the Fair Labor Standards Act’s Section 14(c) and supplemental case studies. The online version included information/resources provided during the in-person training plus assessments to supplement each module; the online version was split into modules to allow participants scheduling flexibility. Participants were given multiple possible attempts to achieve a minimum passing grade of 70%, excluding two ungraded activities (crossword puzzles simply completed). Descriptive statistics evaluated user satisfaction online compared to the in-person version of FWH and performance on aforementioned online assessments replacing in-person discussions/interactions. Results Between October 2013 and April 2015, 160 participants completed the training in person; 156 had complete data. Between April and November 2015, 78 participants completed the training online; 74 participants had complete data. Other enrolled participants were in progress (not done as of 12/23/2015). Overall satisfaction was similarly high for in-person and online versions of FWH; over 95% of responding participants recommended this course to colleagues. Course evaluations for in-person participants indicated 83% felt the course objectives were completely met, whereas 95% of the responding online cohort felt course objectives were completely met. Further analyses examined performance of online assessments regarding number of attempts and scores achieved and performance on highlighted questions in certain module lessons. Conclusion Data suggested the online format as a viable alternative to an in-person version of this training and provided NJSS and agency partners with ideas on how modifications/improvements can be made.